Genotoxic effects of inhaled ethylene oxide, propylene oxide and butylene oxide on germ cells: sensitivity of genetic endpoints in relation to dose and repair status. - Vogel, E.W.; Nivard, M.J.M. (Mutation Research, 1998)
We report here results on forward mutation induction (recessive lethal mutations, RL) in Drosophila spermatozoa and spermatids by the three 1,2-alkyl-epoxides ethylene oxide (EO), propylene oxide (PO) and butylene oxide (BO), at doses ranging from 47 to 24,000 ppm h for EO, 375 to 48,000 ppm h for PO, and 24,000 to 91,200 ppm h for BO. The results indicate for EO mutation induction at doses 500-fold below the LD50. In crosses of mutagenized NER+ males with NER+ females, the 500-fold increase in EO dose from 47 ppm h to 24,000 ppm h resulted in no more than a 17-fold enhanced mutant frequency in spermatozoa. This flat dose-response relationship is primarily the result of efficient repair of EO-induced DNA adducts in the fertilized egg, as was evident from the up to 40-fold or 240-fold increased mutant frequencies above NER- or NER+ background levels, respectively, in crosses with NER- females. With decreasing dose, MNER-/MNER+ ratios decreased from 9 to 14 at high doses down to approximately 1 at the two lowest doses, indicating that a small fraction of premutagenic lesions induced by EO cannot be repaired by the NER system of Drosophila. Linear extrapolation from high to low EO exposure led to an underestimation of the mutation frequency actually observed at low doses. The pattern of EO-induced ring chromosome loss (CL) differed in two respects from that observed for forward mutations: (a) an increase in CL frequencies was observed only at the two highest EO exposure levels, and (b) inactivation of the NER pathway by the mus201 mutant had no measurable effect on the occurrence of CL. The absence of a potentiating effect of mus201 on EO-induced clastogenicity suggests the formation of clastogenic DNA lesions not causing point mutations, and which are not repaired by NER. Consistent with an inversed correlation of reactivities towards N7-guanine and chain length of 1,2-alkyl-epoxides, the relative mutagenic efficiencies of EO:PO:BO are 100:7.2:1.8 for the NER+ groups, and 100:20:0.7 in the absence of NER. Although in Drosophila germ cells EO is also more effective as a clastogen than PO, the difference (EO:PO=100:58) is much smaller than for recessive mutations. These results provide another argument that DNA lesions generating base substitutions as opposed to those causing clastogenic damage may not be the same for these agents.